Epidemiology of vulvar vestibulitis syndrome: an exploratory case-control study. Issue 5 (1st October 1999) - Sarma, A V; Foxman, B; Bayirli, B; Haefner, H; Sobel, J D
Abstract : BACKGROUND: Vulvar vestibulitis syndrome (VVS) is a chronic, persistent syndrome characterised by vestibular pain, tenderness, and erythema. The aetiology of VVS is unknown and few of the hypothesised risk factors have been tested in controlled studies. METHODS: Using a matched case-control study design, medical, sexual, health behaviour, and diet history of 28 women with VVS were compared with 50 friend controls without VVS to identify possible causal factors. RESULTS: Cases were more likely than controls to report every vaginal and urinary symptom at the time of interview measured, particularly vaginal soreness or pain (60.7%) and pain during intercourse (64.3%). There were no significant differences between cases and controls with respect to sexual behaviour. Cases were more likely than controls to report self reported history of physician diagnosed bacterial vaginosis (OR = 22.2, 95% CI = 2.8, 177.2, p value = 0.0001), vaginal yeast infections (OR = 4.9, 95% CI = 1.4, 18.0, p value = 0.01), and human papillomavirus (OR = 7.1, 95% CI = 0.6, 81.2, p value = 0.08). There were no differences between cases and controls with respect to dietary intake of oxalate. Cases were more likely than controls to report poor health status (OR = 5.7, 95% CI = 1.1, 28.7, p value = 0.02) and history of depression for 2 weeks or more during the past year (OR = 4.4, 95% CI = 1.6, 12.3, p value = 0.002). CONCLUSION: Self reported history of bacterial vaginosis, yeast infections, and human papillomavirus were strongly associated with VVS. An infectious origin for VVS should be pursued in larger controlled studies, using questionnaire and laboratory measures.